Experimental and numerical investigation of leading edge Krueger flaps at low Reynolds numbers - Moraris, Vassilis Michael (Cranfield University, 2012)
Recent publications examining the flight of Eagles have shown that leading edge feather deflections occur on the lower surface of the wings in free flight to create a leading edge flap analogous to a Krueger flap system. Such passive high lift devices may be adaptable to the lifting surfaces of unmanned air vehicles (UAVs). This work is aimed to an application of a passive leading edge Krueger device which will deploy during the landing and takeoff stages of a UAV flight. Cont/d.